Adaptasi Kebiasaan Baru Pasca Pandemi pada Pembelajaran Tatap Muka di SD Islam Al-Husna - Aisah Safa Nadhira; Zerri Rahman Hakim; Indhira Asih Vivi Yandari (SAP (Susunan Artikel Pendidikan), 2022)
With the Covid-19 pandemic, the learning process has shifted from distance learning to face-to-face learning, which began to reopen, thus creating a pattern of adjustment to new habits to stop the spread of Covid-19. This study aims to explain the readiness in the implementation of new post-pandemic adaptation activities to face-to-face learning, describe the process of implementing face-to-face learning activities, and reveal the outputs obtained in carrying out face-to-face learning activities at Al-Husna Islamic Elementary School for the 2021-2022 academic year. The research method used is qualitative with a descriptive method, this method is suitable for researchers to describe the entire process of implementing new post-pandemic habit adaptation in face-to-face learning and this research utilize the snowball sampling. The results of this research revealed that SD Islam Al-Husna have fulfilled the readiness based on the Minister's SKB 4 regulations, in the face-to-face learning process, it can be seen that the interaction between teachers and students can be maximized, and the output obtained in face-to-face learning can also be seen that students show a disciplined character with face-to-face learning and students can be more active in learning.